Effect of cellulose-lignin ratio on the adsorption of U(Ⅵ) by hydrothermal charcoals prepared from Dendrocalamus farinosus - Yang, FanQin; Li, Hanhan; Wang, Boya; Fan, Wei; Gu, Xiaoyan; Cao, Ying; Hu, Shanglian (Frontiers in Environmental Science, 2024)
Herein, the impact of varying proportions of cellulose/lignin in bamboo on the production of hydrothermal biochar was investigated. Different characterization techniques were applied to explore the structure of hydrothermal biochar derived from three different genotypes (215, 30-A, 52-B) of Dendrocalamus farinosus, and the adsorption behavior of uranium by these hydrothermal biochars was evaluated. It was found that a decrease in cellulose/lignin ratio (3.08, 2.68, 2.58) positively influenced the specific surface area and pore volume of hydrothermal biochar. Consequently, the prepared hydrothermal biochars exhibited adsorption capacities for U(VI) ions at levels of 14.78 mg/g, 24.68 mg/g, and 26.02 mg/g respectively under these three ratios. The adsorption process by 52-B-220 well complied with the Freundlich isotherm, which indicated that the multi-layer adsorption occurred on the solid liquid interface, but single-layer adsorption was evident in those prepared from genotypes 30-A and 215.This study demonstrated that adjusting biomass feedstock composition as an effective strategy for enhance the quality of biochar.